2020
DOI: 10.1016/j.agsy.2020.102948
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen-fertilizer and optimal plant population on the profitability of maize plots in the Wami River sub-basin, Tanzania: A bio-economic simulation approach

Abstract: Maize ( Zea mays L. ) is the essential staple in sub-Saharan Africa (SSA) and Tanzania in particular; the crop accounts for over 30% of the food production, 20% of the agricultural gross domestic product (GDP) and over 75% of the cereal consumption. Maize is grown under a higher risk of failure due to the over-dependence rain-fed farming system resulting in low income and food insecurity among maize-based farmers. However, many practices, including conservation agriculture, soil and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The theory on diffusion of innovation was relevant as Gliricidia agroforestry intercropping is a new technology that can spread within the community. Feder et al [60], Rogers [61], Kadigi et al [8], and Swamila et al [4] argue that individual farmers' adoption of improved agricultural technologies in a long-run equilibrium depends on access to full information about relative advantages. According to [45,62], a relative advantage of this technology compared to others is its short (≤5 years) and long-term (>10 years) profitability.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The theory on diffusion of innovation was relevant as Gliricidia agroforestry intercropping is a new technology that can spread within the community. Feder et al [60], Rogers [61], Kadigi et al [8], and Swamila et al [4] argue that individual farmers' adoption of improved agricultural technologies in a long-run equilibrium depends on access to full information about relative advantages. According to [45,62], a relative advantage of this technology compared to others is its short (≤5 years) and long-term (>10 years) profitability.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…The sustainable productivity of field crops such as cereals and pulses in most dryland areas of sub-Saharan Africa (SSA) is limited by declining soil fertility and high vulnerability to weather and natural disasters [1][2][3][4]. Most cereal food crops such as maize are produced under low nitrogen (N) and phosphorous (P) conditions that have contributed to the yield gap of between 200% and 300% [5][6][7][8]. Additionally, maize yields are sensitive to changes in climate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that improved irrigation and N management practices as suggested by the DSSAT-CERES-maize model could improve maize yield and N use efficiency under Mediterranean climate conditions. Kadigi et al (2020) used DSSAT to evaluate the economic feasibility of an improved planting density (used to realize an optimized plant population) and better N-fertilizer crop management practices for increasing maize net returns in semi-arid and sub-humid agro-ecological zones in the Wami River sub-Basin in Tanzania. Finally, Banger et al (2018) used the DSSAT-CERES maize model to analyze the impact of N management on maize yield in the Midwest region of the U.S.…”
Section: Introductionmentioning
confidence: 99%